Enterococcus faecalis endophthalmitis as a metastatic complication of hemodialysis vascular access‐related sepsis: A case report and review of the literature. Issue 3 (7th September 2015) - Sahin, Osman Zikrullah; Kara, Ekrem; Belice, Tahir; Ayaz, Teslime; Baydur Sahin, Serap; Ozturk, Cinar; Yildirim, Safak; Metin, Yavuz; Sahutoglu, Tuncay
Abstract: Catheter and/or arteriovenous (A‐V) graft‐related bacteremia is an important cause of morbidity and mortality among hemodialysis (HD) patients. Endocarditis, septic arthritis, epidural abscess, septic embolism, and osteomyelitis are the most common complications of catheter and/or A‐V graft‐related bacteremia; however, endogenous endophthalmitis is rarely seen. To the best of our knowledge, E nterococcus faecalis is the first case report in this population. We hereby report a case of endogenous endophthalmitis caused by E . faecalis as a complication of catheter and/or A‐V graft‐related bacteremia in a diabetic patient, who was undergoing HD for 5 years. We also discuss the etiology, clinical features, and outcomes of endogenous endophthalmitis in HD patients with a brief review of the literature. Although broad‐spectrum parenteral (intravenous and intravitreal) antibiotics were used for 4 weeks, evisceration of the left eye could not be avoided. Endogenous endophthalmitis is a rare but rapidly blinding complication of catheter and/or A‐V graft‐related bacteremia in HD patients. It can develop as a result of silent catheter and/or A‐V graft infections, which may lead to recurrent bacteremia. E . faecalis should be considered as a pathogen in this population who had recent history of catheter or A‐V graft procedure.